2010
DOI: 10.2104/aral1029
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of L2 English morphology

Abstract: This study investigates the status of morphology in the L2 English of three members of a family from Indonesia (parents and their 5-year-old daughter) who have lived, studied or worked in Australia for a year. The investigation is contextualized against various learning settings in which the informants have learned English: formal instruction in the foreign language environment, naturalistic learning in the target language setting, and a mixture of formal and naturalistic learning in the target language enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(15 citation statements)
references
References 20 publications
0
14
0
1
Order By: Relevance
“…With reference to Dao's (2007) findings, Charters et al (2011) conducted a further discussion using a speech processing model called Weaverþþ (Levelt, Roelofs, & Meyer, 1999) and clarified that this counterevidence to L1 transfer was still within range of PT's Developmentally Moderated Transfer Hypothesis that "one can only transfer what can be processed" (Pienemann & Kebler, 2011, p. 75). Zhang and Widyastuti (2010) also empirically revealed L1 transfer in L2 morphological use within the PT framework. They investigated English L2 morphological development for an Indonesian L1 family (N ¼ 3).…”
Section: Empirical Studies Testing Pt Predictionmentioning
confidence: 86%
See 1 more Smart Citation
“…With reference to Dao's (2007) findings, Charters et al (2011) conducted a further discussion using a speech processing model called Weaverþþ (Levelt, Roelofs, & Meyer, 1999) and clarified that this counterevidence to L1 transfer was still within range of PT's Developmentally Moderated Transfer Hypothesis that "one can only transfer what can be processed" (Pienemann & Kebler, 2011, p. 75). Zhang and Widyastuti (2010) also empirically revealed L1 transfer in L2 morphological use within the PT framework. They investigated English L2 morphological development for an Indonesian L1 family (N ¼ 3).…”
Section: Empirical Studies Testing Pt Predictionmentioning
confidence: 86%
“…However, the latest PT publications have explicitly hypothesized that the development of syntax and morphology has two separate motivations (Di Biase & Kawaguchi, 2013;Pienemann & Kebler, 2012;Yamaguchi, 2013). In this context, recent cross-sectional and longitudinal studies on English L2 learners have demonstrated the effects of L1 influence and individual variation on morphological development (Charters, Dao, & Jansen, 2011;Dao, 2007;Dyson, 2009;Zhang & Widyastuti, 2010). Meanwhile, other longitudinal child L2 studies have confirmed PT prediction (Yamaguchi, 2013;Yamaguchi & Kawaguchi, 2014).…”
Section: Introductionmentioning
confidence: 93%
“…Australian SLA research in the reviewed period has also covered a diverse range of areas including that with a focus on: vocabulary (e.g. Harrington & Jiang 2013; Van Zeeland 2013); morphology (Zhang & Widyastuti 2010); feedback (e.g. written feedback – Bloomfield 2013); affective factors (e.g.…”
Section: Sla and Pedagogymentioning
confidence: 99%
“…However, because the quantity and quality of the input is affected by many factors, exposure to the target language may not be as much as expected (Norton, 2000;Goldstein, 2001). L2 also plays a role in language acquisition, where the extent of acquisition of the language depends on L2 proficiency (Zhang & Widyastuti, 2010).…”
Section: Background To the Studymentioning
confidence: 99%